Amino acid sequence homologies between the high-mobilitygroup proteins, HMG-T from trout testis and HMG-1 and-2 from calf thymus: is the poly-aspartic-glutamic acid polypeptide within the main chain?. Issue 2 (February 1981) - Watson, D. C.; Dixon, G. H.
Abstract : The amino acid sequence of the N-terminal two-thirds of a trout high-mobility-group protein, HMG-T, has been determined as a continuous sequence of 174 residues out of a total for the whole molecule of 260 residues. When this sequence was compared with published sequences of long cyanogen bromide-derived peptides from the analogous calf-thymus proteins, HMG-1 and −2 (Walker et al., 1979), there was strong homology, with 60–70% identity of corresponding amino acid residues in the three proteins, the majority in lengthy identical runs. However, a discrepancy in the position of a highly acidic run of aspartic and glutamic residues suggests this region may not lie within the main polypeptide chain but may represent a separate chain or possibly a branched structure,